First results of using the second generation SBAS in Australian urban and suburban road environments. Issue 1 (2nd January 2020) - El-Mowafy, Ahmed; Cheung, Norman; Rubinov, Eldar
ABSTRACT: In this study, the first results of the next-generation dual-frequency multi-constellation SBAS-based kinematic positioning in Australian urban environments are presented and analysed. As the standalone GNSS positioning is unable to deliver the accuracy required for absolute positioning in Intelligent Transport Systems (ITS), more advanced technologies are needed, and the Australian SBAS with PPP capabilities is a candidate. Kinematic tests were run in scenarios characterised by four environments: high-density urban, low-density urban, suburban and tree-canopy. SBAS positioning performance was evaluated in the different environments, with a focus on its capability to provide lane identification and thus aid ITS applications.